Individual differences in athletes' perception of expressive body movements. (May 2016) - Sevdalis, Vassilis; Raab, Markus
Abstract: Objectives: Understanding others' actions depends on the observer's individual characteristics and sensorimotor experience. Motor performance domains, such as sports and the performing arts, provide optimal situations to investigate the determinants of action perception. We investigated athletes' perceptual identification of expression intensity in body movements. Design: A within-subjects design was used. Method: Participants watched point-light displays (1000 ms long) depicting expressive and inexpressive dance movements. The task was to identify the dancer's intended expression intensity. Results: The results indicate that expressive body movements can be reliably identified, with judgement accuracy correlating with self-report empathy indices, intuitive/deliberate decision-making preferences, and indices of sports training. Only years of sports training could predict perceptual identification accuracy. Conclusions: We discuss the findings in relation to motor and cognitive–emotional contributions to action simulation. The potential of cross-domain transfer of motor expertise for boosting perceptual judgements and a hierarchical role of factors eliciting action simulation are also outlined. Highlights: We investigated athletes' perceptual identification of expression intensity in body movements. Judgement accuracy correlated with self-report empathy, decision-making preferences, and indices of sports training. Only years of sports training could predict perceptual identification accuracy. Sensorimotor and cognitive-emotional contributions to action simulation are discussed.